Acoustic emission and CT investigation on fracture evolution of granite containing two flaws subjected to freeze–thaw and cyclic uniaxial increasing-amplitude loading conditions. (10th November 2020) - Wang, Y.; Han, J.Q.; Li, C.H.
Highlights: The previous F-T damage impacts the mechanical properties of granite samples. The accumulative AE count/energy decreases with increasing number of F-T cycles. Large scale cracks are prone to forming for rock high F-T treatment from spectral analysis. The pre-flaws are easy to be communicated when experiencing high F-T treatment. Abstract: The deterioration mechanism and fatigue fracturing evolution of granite with two pre-existing flaws experiencing freeze–thaw (F-T) treatment are investigated in this work. The flaws in the rock sample were prepared as a combination of a horizontal flaw with an upper inclined flaw above the horizontal flaw according to the joint characteristics in an open pit slope. In-situ acoustic emission monitoring combined with the post-test 3D computed tomography (CT) technique was employed to reveal the fracture evolution behaviors of rock treated with 0, 50, and 80 freeze–thaw cycles. Results show that the freeze–thaw damage impacts the frost heaving force, cyclic deformation, AE activates, crack coalescence pattern and fatigue life of the granite samples. The accumulative AE count/energy decreases with increasing number of freeze–thaw cycles, and the accumulated AE count/energy in a loading stage gradually grows faster. In addition, AE spectral frequency analysis reveals the impact of previous freeze–thaw damage on the formation of the crack scale, the sample is prone to producing large scale cracks under high freeze–thaw treatment. Moreover, 3D reconstructed CT images present an internal crack network pattern, and the most striking finding is that a simple crack network forms for a sample experiencing high F-T fatigue damage. It is suggested that deterioration of the rock bridge structure is strongly impacted by the accumulative freeze–thaw damage. The testing results are helpful to understand the influence of freeze–thaw and fatigue loading on the fracture evolution characteristics of rock in cold regions.